PLA-Based Mineral-Doped Scaffolds Seeded with Human Periapical Cyst-Derived MSCs: A Promising Tool for Regenerative Healing in Dentistry - Tatullo, Marco (Materials (Basel), 2019)
Human periapical cyst mesenchymal stem cells (hPCy-MSCs) are a newly discovered cell population innovatively collected from inflammatory periapical cysts. The use of this biological waste guarantees a source of stem cells without any impact on the surrounding healthy tissues, presenting a valuable potential in tissue engineering and regenerative medicine applications. In the present study, hPCy-MSCs were collected, isolated, and seeded on three experimental mineral-doped porous scaffolds produced by the thermally-induced phase-separation (TIPS) technique. Mineral-doped scaffolds, composed of polylactic acid (PLA), dicalcium phosphate dihydrate (DCPD), and/or hydraulic calcium silicate (CaSi), were produced by TIPS (PLA-10CaSi, PLA-5CaSi-5DCPD, PLA-10CaSi-10DCPD). Micro-CT analysis evaluated scaffolds micromorphology. Collected hPCy-MSCs, characterized by cytofluorimetry, were seeded on the scaffolds and tested for cell proliferation, cells viability, and gene expression for osteogenic and odontogenic differentiation (DMP-1, OSC, RUNX-2, HPRT). Micro-CT revealed an interconnected highly porous structure for all the scaffolds, similar total porosity with 99% open pores. Pore wall thickness increased with the percentage of CaSi and DCPD. Cells seeded on mineral-doped scaffolds showed a superior proliferation compared to pure PLA scaffolds (control), particularly on PLA-10CaSi-10DCPD at day 12. A higher number of non-viable (red stained) cells was observable on PLA scaffolds at days 14 and 21. DMP-1 expression increased in hPCy-MSCs cultured on all mineral-doped scaffolds, in particular on PLA-5CaSi-5DCPD and PLA-10CaSi-10DCPD. In conclusion, the innovative combination of experimental scaffolds colonized with autologous stem cells from periapical cyst represent a promising strategy for regenerative healing of periapical and alveolar bone.